2017
DOI: 10.1016/j.conbuildmat.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nano graphite platelets-enabled piezoresistive cementitious composites for structural health monitoring

Abstract: This paper studied the piezoresistive effects of cementitious composites filled with nano graphite platelets (NGPs). Experiments are performed to investigate the electrical responses of cementitious composites filled with NGPs when subjected to cyclic compressive stress under different quasi static and dynamic loading conditions such as different loading amplitudes, different loading rates and constant loading within the elastic regime of these composites. Meanwhile, the cementitious composites filled with NGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(71 citation statements)
references
References 37 publications
0
70
0
1
Order By: Relevance
“…81,82 GFCC also possess excellent piezoresistivity effect. Sun et al 79 investigated the relationship between compressive strain and change in electrical resistance of cementitious composites with GNP. As shown in Figure 5(a), the larger the compression strain is, the more the resistance of GFCC decreases.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 GFCC also possess excellent piezoresistivity effect. Sun et al 79 investigated the relationship between compressive strain and change in electrical resistance of cementitious composites with GNP. As shown in Figure 5(a), the larger the compression strain is, the more the resistance of GFCC decreases.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…But the linear performance appeared only when the GNP concentration exceeded 2.4 vol.%, which Pang et al pointed out as the percolation threshold value of the composites. Sun et al 79 tested the repeatability of this piezoresistive behavior and found it repeated stably under lots of times of cyclic quasi-static compressive loading and dynamic cyclic loading within elastic regime. Moreover, the amplitudes of change in the electrical resistivity of the composites showed a little decrease with test time at high loading rate, which means the piezoresistivity is slightly dependent on the dynamic loading rate.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Finally, carbon nanomaterials gathered a lot of attention as they have, beyond high electrical conductivity, unique physical properties [16,29]. Among carbon nanomaterials employed in concrete composites we mention carbon black [30,31], carbon nanotubes [32][33][34][35] and nanofibers [36][37][38][39][40], as well as graphene nanoplatelets [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Su introducción en sistemas cementicios puede mejorar sus propiedades en estado endurecido de forma más eficiente que con las nanofibras o nanotubos de carbono y mejor relación coste-beneficio [10]. Además de una mejor resistencia a compresión, a tracción o en flexotracción [11], la reducida resistividad eléctrica de las GNPs podría explotarse en el desarrollo de estructuras de hormigón capaces de automonitorizarse [12]. El principal problema asociado a las GNPs vuelve a ser su dispersabilidad [13].…”
unclassified